2018
DOI: 10.1016/j.jaut.2018.08.007
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review on the role of co-signaling receptors and Treg homeostasis in autoimmunity and tumor immunity

Abstract: The immune system ensures optimum T-effector (Teff) immune responses against invading microbes and tumor antigens while preventing inappropriate autoimmune responses against self-antigens with the help of T-regulatory (Treg) cells. Thus, Treg and Teff cells help maintain immune homeostasis through mutual regulation. While Tregs can contribute to tumor immune evasion by suppressing anti-tumor Teff response, loss of Treg function can result in Teff responses against self-antigens leading to autoimmune disease. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(119 citation statements)
references
References 369 publications
(421 reference statements)
3
116
0
Order By: Relevance
“…In effector CD4 + T cells, the predominated conclusion is triggering GITR on CD4 + CD25 - T cells can induce the survival, activation and proliferation of CD4 + T cells, and the effect is mainly dependent on TCR stimulation and CD28 co-triggering ( 13 ). However, several researches reported that GITR/GITRL interaction could also contribute to immune homeostasis by regulating effector CD4 + T cells ( 14 , 15 ). GITR engagement can mediate cell apoptosis.…”
Section: Effect Of Gitr On Effector T Cellsmentioning
confidence: 99%
“…In effector CD4 + T cells, the predominated conclusion is triggering GITR on CD4 + CD25 - T cells can induce the survival, activation and proliferation of CD4 + T cells, and the effect is mainly dependent on TCR stimulation and CD28 co-triggering ( 13 ). However, several researches reported that GITR/GITRL interaction could also contribute to immune homeostasis by regulating effector CD4 + T cells ( 14 , 15 ). GITR engagement can mediate cell apoptosis.…”
Section: Effect Of Gitr On Effector T Cellsmentioning
confidence: 99%
“…Within the TNFR family, we selected: 4-1BB as this co-receptor is beneficial for the longevity of CAR-T cells (Long et al, 2015;Song et al, 2011) and in models of autoimmunity is beneficial for Tregs (Kumar et al, 2018); OX40 and GITR, which promote Tregs in certain contexts (Kumar et al, 2018); and TNFR2 which stimulates Treg proliferation and suppression Pierini et al, 2016).…”
Section: Generation Cell Surface Expression and Selection Of Signalimentioning
confidence: 99%
“…Due to the extensive evidence for the important role of CD28 co-stimulation in Tregs (Esensten et al, 2016), the majority of CAR-Treg studies selected this protein as the source of co-stimulation. However, as with conventional T cells (Tconvs), Tregs express a number of coreceptors that provide co-stimulatory or co-inhibitory signals (reviewed in (Kumar et al, 2018)), the functional relevance of which may differ from that in Tconvs, and vary depending on the tissue/disease context. An additional consideration is that the vast majority of studies which have defined co-receptor function in Tregs used genetic-deletion models in which co-receptors of interest were absent throughout Treg development, thus making it difficult to infer function in the fully differentiated cells which would be used for CAR engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Early recognition and quick intervention, for instance with corticosteroids, is essential. A previous comprehensive review focused on the role of cosignaling (costimulatory or co-inhibitory) receptors and Treg homeostasis in autoimmunity and tumor immunity ( 64 ).…”
Section: Successful Cancer Immunotherapymentioning
confidence: 99%